Advanced glycosylation products quench nitric oxide and mediate defective endothelium-dependent vasodilatation in experimental diabetes. - Bucala, R; Tracey, K J; Cerami, A (The Journal of Clinical Investigation, 1991)
Nitric oxide (an endothelium-derived relaxing factor) induces smooth muscle relaxation and is an important mediator in the regulation of vascular tone. Advanced glycosylation end products, the glucose-derived moieties that form nonenzymatically and accumulate on long-lived tissue proteins, have been implicated in many of the complications of diabetes and normal aging. We demonstrate that advanced glycosylation products quench nitric oxide activity in vitro and in vivo. Acceleration of the advanced glycosylation process in vivo results in a time-dependent impairment in endothelium-dependent relaxation. Inhibition of advanced glycosylation with aminoguanidine prevents nitric oxide quenching, and ameliorates the vasodilatory impairment. These results implicate advanced glycosylation products as important modulators of nitric oxide activity and endothelium-dependent relaxation.